Effects of milk powder fortified with red ginseng extracts on the skin barrier function and immunity of middle-aged women - Yao Ge; Wenhui Ye; Yue Wang; Aiqin Ma; Man Wang; Qingshan Chen; Xiaoyan Huo; Chunxi Liu; Yujie Shi; Biao Liu; Wei Chen (Journal of Functional Foods)
This study investigated the effects of a nutritional milk composition containing red ginseng extract (MCCRG) on the skin barrier function and immunity of middle-aged women. Fifty women (aged, 25 to 45) consumed MCCRG orally for 56 days. Evaluations of skin phenotype, facial bacterial microbiome, immune system function, and clinical diagnoses were conducted. The results indicated that MCCRG significantly improved skin hydration, firmness, elasticity, and glossiness. Furthermore, MCCRG also reduced TEWL and wrinkles and enhanced skin barrier integrity. Additionally, high IgG levels and improved CD4+/CD8+ ratios due to MCCRG consumption increased facial microbiota diversity and immune function. Clinical diagnoses provided supplementary evidence for the efficacy of MCCRG. The findings of this study demonstrated that MCCRG, through nutritional support, enhanced both skin barrier and immune system functions. This study offers substantial evidence of the innovative therapeutic effects of nutritional support on skin barrier damage and immune function.